The hospital-based incidence of influenza infection in children with type C symptoms: an observational study - Masood, Ashfaq; Paul, Bilal Ahmad; Ahmed, Syed Basharat; Tramboo, Zubair Mushtaq; Bhat, Javeed Iqbal (International Journal of Contemporary Pediatrics, 2025)
Background: Influenza, a contagious respiratory illness, poses a significant threat to children, especially those with severe symptoms (Category C). This study aimed to investigate the hospital-based incidence, clinical profile, and outcomes of influenza in pediatric patients. Methods: This prospective cross-sectional study was conducted from June 2019 to August 2021, enrolling 220 children (6 months to 18 years) with category C influenza-like symptoms. Influenza was diagnosed via reverse transcription polymerase chain reaction (RT-PCR) using nasopharyngeal and oropharyngeal swabs. Clinical data, laboratory findings, and treatment outcomes were analyzed. Results: Influenza was detected in 47 (21.63%) patients, with peak incidence in October 2019 and February 2020. No cases were recorded in 2021. No significant differences were observed between influenza-positive and-negative groups in demographics or clinical symptoms. ICU admission was higher in the influenza-positive group (14.9% vs. 1.7%). Mortality was significantly higher in influenza-positive patients (12.8% vs. 1.2%). Vaccination rates were low (2.3%). Conclusions: Influenza poses a considerable health burden in children with severe respiratory symptoms, with increased mortality in positive cases. The marked decline in influenza cases during the COVID-19 pandemic highlights the effectiveness of public health measures. Clinicians should consider influenza in the differential diagnosis of children with severe respiratory illness, particularly during winter. Low vaccination rates emphasize the need for improved vaccination strategies.